The system of carbon tetrachloride and closed carbon nanotubes analyzed by a combination of molecular simulations, analytical modeling, and adsorption calorimetry - Furmaniak, S.; Terzyk, A.; Rychlicki, G.; Wisniewski, M.; Gauden, P.; Kowalczyk, Poitr; Werengowska, K.; Dulska, K. (Elsevier, 2010)
Using the combined techniques of molecular simulation, simple analytical modeling, and adsorption calorimetry, we propose new models describing adsorption onto closed carbon nanotubes. The models are capable of describing the adsorption isotherms and calorimetric enthalpy of carbon tetrachloride adsorption measured on three different closed carbon nanotubes. It is shown that the assumption of the presence of two types of surface centers (high- and low-energy centers) on external tube surfaces is sufficient to describe experimental adsorption and calorimetric enthalpy data